2009
DOI: 10.2319/080708-410.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Buccal Corridors on Smile Esthetics in Japanese

Abstract: The hypothesis was rejected. Both the orthodontists and dental students preferred broader smiles to medium or narrow smiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
6
9

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 16 publications
7
78
6
9
Order By: Relevance
“…5,6 During interpersonal interaction, it is most common for individuals to focus on the other person's eyes and mouth and give less attention to other facial characteristics. 7 The teeth are considered the most important components in the facial architecture, 8 and a harmonious smile plays an important role in establishing physical and facial beauty. 9 Attractiveness causes positive emotional reactions in the observer, creating desires to establish affective/ romantic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 During interpersonal interaction, it is most common for individuals to focus on the other person's eyes and mouth and give less attention to other facial characteristics. 7 The teeth are considered the most important components in the facial architecture, 8 and a harmonious smile plays an important role in establishing physical and facial beauty. 9 Attractiveness causes positive emotional reactions in the observer, creating desires to establish affective/ romantic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][23][24][25][26] In the literature, digitally altered images have often been created from a single image of the same patient to obtain a variety of sizes of the buccal corridor. [9][10][11][12][23][24][25][26] However, studies on the buccal corridor with nonmanipulated photographs 13,27 have failed to report a correlation between the buccal corridor and smile attractiveness. Janson 6 recently reviewed previous articles on this matter and concluded that images of actual patients are more acceptable SMILE ATTRACTIONS than digitally altered smiles.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 An equal number of male and female evaluators were used. [10][11][12] According to the method of McNamara et al, 13 selected images were printed on evaluation sheets at a fixed width of 100 mm along with a 100-mm visual analogue scale (VAS) (Figure 2), which was used by the students to evaluate the attractiveness of the images. Student evaluations were measured in millimeters from the left end of the 100-mm bar using a digital caliper (NTD12-15CX; Mitutoyo, Kawasaki, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…12 Las preferencias del corredor bucal para personas con y sin conocimiento de ortodoncia fueron estrecho y medio estrecho, resultados similares a los estudios publicados por Moore y col, Ioi y colaboradores, Martin y colaboradores, y Parekh y colaboradores. 1,3,19,21 Por el contrario, Ritter y colaboradores no hallaron mayor influencia en la estética de la sonrisa ni diferencia en la evaluación entre ortodoncista y personas del común en relación con un corredor bucal amplio. 22 Cabe señalar que los datos proporcionados en el estudio son el resultado del análisis de la fotografía solo de la región de sonrisa y no de una fotografía de cara completa.…”
Section: Artículo De Investigación Científica Y Tecnológicaunclassified
“…La importancia de una sonrisa atractiva ha variado con el pasar de los años y recientemente la evaluación de esta ha despertado un gran interés por parte de los clínicos, llevándolos a evaluar variables como el corredor bucal y la coincidencia de la línea media dental, a pesar de la poca evidencia científica existente. [1][2][3][4][5][6][7][8] La evaluación del perfil facial en el diagnóstico ortodóncico ha tenido hasta ahora mayor relevancia que la evaluación de la sonrisa. 8 Así por ejemplo, en el aniversario número 100 de la Sociedad Americana de Ortodoncia el logo fue "Ortodoncia 100 años de Sonrisa" y si se busca en Medline desde 1967 hasta 2008 con palabras clave como "Orthodontics" y "Smile" se encuentran solo 23 referencias; por el contrario, si se busca "Orthodontics" y "Facial profile" se hallan 153 artículos.…”
Section: Introductionunclassified